2020
DOI: 10.47836/pjssh.28.4.44
|View full text |Cite
|
Sign up to set email alerts
|

Where to Eat: Exploring Silver Consumer Restaurant Dining Choice in Malaysia

Abstract: Eating out among older adults are becoming the norm due to its convenience and potential for social interaction. Malaysia is expected to become an aged nation whereby 14% or more of its population will be 65 years and older by 2050. Very little is known about restaurant preferences and patronage behaviours of older adults in Malaysia even though there had been numerous researches done involving this population. It is important to acknowledge this age group not just because they are living longer; but also, bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Of the seven domains of age‐friendly dining identified in the workshops, five (Menu, Affordability, Venue, Feeling Welcome and Assistance) are echoed in other studies. Good food, service, venue/location were all important in Bakar et al’s Malaysian study 4 . They also identified an additional factor of socialising and companionship.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Of the seven domains of age‐friendly dining identified in the workshops, five (Menu, Affordability, Venue, Feeling Welcome and Assistance) are echoed in other studies. Good food, service, venue/location were all important in Bakar et al’s Malaysian study 4 . They also identified an additional factor of socialising and companionship.…”
Section: Discussionmentioning
confidence: 92%
“…Good food, service, venue/location were all important in Bakar et al's Malaysian study. 4 They also identified an additional factor of socialising and companionship. Two of the strongest motivations for older consumers to eat out are convenience and companionship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the location of senior-friendly restaurants must be carefully chosen to ensure that the majority of senior residents within the community are encompassed within their service area. The convenience of a senior-friendly restaurant's location significantly influences seniors' willingness to dine in, as indicated by recent research [23]. Senior citizens tend to engage in multiple activities when they go out.…”
Section: Introductionmentioning
confidence: 99%
“…Elderly and young people differ significantly in terms of dining because of differences in age, physical fitness, and other factors. A study of 'silver consumers' in Malaysia found that elderly people living in households were more conscious of food quality and service when eating out (Bakar et al, 2020). Older people living in geriatric care homes will also expect a restaurant-style experience, but will value stable table companions over flexibility (Kenkmann and Hooper, 2012).…”
Section: Introductionmentioning
confidence: 99%